PENGARUH MODEL PROJECT BASED LEARNING DENGAN LIVE AQUARIUM MENGGUNAKAN SPESIES ASLI INDONESIA TERHADAP HASIL BELAJAR KOGNITIF SISWA PADA MATERI EKOSISTEM - Riska Septia Wahyuningtyas (Jurnal Pro-Life, 2019)
This research aims to determine the effect of using Project Based Learning models with Live Aquarium which uses native Indonesian species on cognitive study result. The research design is a quasi-experiment that uses a pretest posttest control group design model. The research population was all seventh grade students in Yogyakarta Junior High School 1 consist of 8 classes. The research sample was taken two classes based on cluster random sampling technique. The control class is VII A and the experimental class is VII B. The instruments that used in this study were observation sheets of learning implementation with the PjBL model and the pretest and posttest to find out the cognitive study result. The data from this research were analyzed by ANOVA test. The results showed that learning with the Project Based Learning learning model with Live Aquarium that uses native Indonesian species had a positive effect on cognitive study result. Keywords: cognitive study result, project-based learning, student.